Legal Protection Of The Gorontalo City Police Against Debtors Who Transfer Fiduciary Vehicles Without The Consent Of The Fiduciary Recipient - Puluhulawa, Sitty Masitha Syeila; W. Badu, Lisnawaty; Meiske Kamba, Sri Nanang (Estudiante Law Journal, 2024)
The purpose of writing this article is to determine the efforts that can be prevented by the police against fiduciary acts in the transfer of fiduciary objects in the jurisdiction of Gorontalo City. The method used in this study is to use empirical research methods with a qualitative approach. HasiL research on this case fiduciary receiver or 2nd party raises the issue of the possibility of a crime in the field of fiduciary. This event is where the 2nd party makes a car loan at a financing company or individual with an installment payment system in accordance with the agreement specified in the agreement and for a certain time. In fact, after the credit agreement is running, the 2nd party (fiduciary recipient) does not perform its obligations as agreed between the twelve fiduciary parties to the fiduciary recipient to pay the installments, but resells the goods that are the object of fiduciary security to the 3rd party without the knowledge of the 3rd party whose vehicle is still in the installment financing 2nd (fiduciary recipient) to the First party (fiduciary giver).